Penggunaan Media Ular Tangga Dalam Menganalisa Keefektifan Peningkatan Kemampuan Numerasi Siswa SD N 2 Tanjung Dalam Program Kampus Mengajar - Exwan Andriyan Verrysaputro; Ira Sri Rahayu; Wiwit Cipta Indah Lestari; Aninda Nisha Agrestia (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Ular Tangga learning media is a fun learning tool. The use of this learning media is carried out through a learning concept combined with play. Based on the preliminary study conducted on fifth-grade students at SD N 2 Tanjung, it was found that teachers did not use learning media in students' numeracy learning. This study aims to determine the extent to which Ular Tangga media is effective in improving students' numeracy skills at SD N 2 Tanjung. This research uses a qualitative research design with a case study approach. The population in this study is fifth-grade students at SD N 2 Tanjung. The participant determination technique used in this study is purposive sampling technique with a total of 13 students participating. The results of this study indicate that the application of the Ular Tangga media is effectively used. This can be seen from the interview results and the pretest results when using conventional methods, where only 25% of students obtained results above the predetermined minimum passing grade. After the post-test, there was a significant improvement, with 88,44% of students achieving scores above the minimum passing grade.